Prospects for the Welfare State - Assar Lindbeck (Research Institute of Industrial Economics (IFN), 2008)
It is useful to distinguish between exogenous and endogenous factors behind contemporary and expected future problems for the welfare state. This paper tries to identify major problems of both types and to indicate alternative reform possibilities to deal with them. At the same time as several governments struggle with such reforms, new demands on the welfare state emerge. Although the basic structure of todays welfare-state arrangements certainly can be kept, the reforms required are sufficiently large to create considerable conflicts across interest groups.
Keywords: H40; H50; I38; 330; Welfare State; Social Insurance; Human Services; Sozialstaat; Sozialpolitik; Sozialreform; Sozialversicherung; Öffentliche Güter; Öffentliche Ausgaben; Westeuropa